An uncommon 3D 3, 3, 4, 8-c Cd(ii) metal–organic framework for highly efficient luminescent sensing and organic dye adsorption: experimental and theoretical insight. Issue 46 (14th November 2017) - Lu, Lu; Wu, Jian; Wang, Jun; Liu, Jian-Qiang; Li, Bao-Hong; Singh, Amita; Kumar, Abhinav; Batten, Stuart R.
Abstract : A stable 3D Cd(ii ) MOF used as chemosensor and adsorbent for dyes in wastewater, which exhibited excellent adsorption performance and selectivity. Abstract : A new Cd(ii ) based metal–organic framework (MOF), having formula (CH3 )2 NH2 )6 [Cd5 (L)4 ]·H2 O·3DMF n (1 ), has been synthesized based on a rigid tetracarboxylate ligand of terphenyl-3, 3′′, 5, 5′′-tetracarboxylic acid (H4 L).1 shows a complicated 3D tetranodal 3, 3, 4, 8-c network with uncoordinated –COO − groups. The highly selective luminescent sensing of 2, 4-dinitrophenol (2, 4-DNP), 2, 4, 6-trinitrophenol (TNP) and ferric ions was studied for1 through the alleviation in its fluorescence intensity. The detection limit of 2, 4-DNP was found to be 0.84 ppm, which is 20 times higher than that of 1, 3, 5-trimethylbenzene, demonstrating greater and selective quenching ability. The possible mechanism associated with the decrease in fluorescence intensity of1 in the presence of nitroaromatics (NACs) has been addressed by theoretical calculations. Furthermore, 1 displays excellent capacity to adsorb methylene blue (MB) with high selectivity, and it maintains an almost identical adsorption performance after being recycled five times.